DEVELOPMENT OF NON-UPTITUDE CREATIVITY IN EARLY CHILDHOOD THROUGH WASTE, NATURAL AND SYNTHETIC MEDIA (LOOSE PARTS) IN RA MAMBA'UL HIKMAH JEMBER - Muzayyanah; Nurul Anam; Fathor Rahman (FORPIM PTKIS ZONA TAPAL KUDA, 2022)
ABSTRACTIn the era of society 5.0, the development of early childhood creativity is very significant. The reality that is very worrying is that many children are starting to become contaminated with online games, so that these games make them forget to study and even make them die. Events like this should be avoided in early childhood. Early childhood must be taught to be able to develop their creativity through learning media or other more educative games. One of them is that the media uses waste, natural and synthetic materials that have been implemented well at RA Mamba'ul Hikmah. From this background, this research is focused on efforts to describe the development of non-uptitude creativity in early childhood media through the media of waste, natural and synthetic materials at RA Mamba'ul Hikmah. The research method uses a qualitative approach and the type of research is a case study. The results of his research show that the contribution of the media to the development of non-uptitude creativity in early childhood is very good because the media is used by introducing various kinds of media, building children's curiosity, using them in a variety of ways and giving children the freedom to explore according to their ideas and desires. From a process like this, children can increase non-uptitude creativity, among others, have curiosity, imagination, feel challenged and dare to take risks.Keywords: Non Uptitude Early Childhood Creativity, Loose Parts